Research on the effects and related mechanisms of geomagnetic storm on depression - Hui Wu; Yuan Yang; Weiyu Chang; Xinli Chen; Shiqi Yang; Min Xu; Keyu Liu; Yu Yun; Liang Dong (Brain Research Bulletin)
Objective: Depression has become disabling disease in the world. Geomagnetic storm is closely related to depression behavior, and melatonin is an important factor in the pathogenesis of depression. This study observed the effects of different intensities of geomagnetic storm on melatonin in depressed rats. Aim to provides a theoretical basis for the prevention and treatment of depression and other melatonin related mental illnesses during geomagnetic storms. Methods: In this study, rats with chronic unpredictable mild stress (CUMS) were exposed to geomagnetic storms of different intensities for 7 days. The depressive behavior of CUMS rats was determined via the weigh, sucrose preference test, elevated plus maze test, novelty-suppressed feeding test and open field test. Then, through the use of kits, qPCR analysis, immunofluorescence staining and western blot analysis of melatonin synthesis, melatonin metabolism and melatonin receptor pathway related indicators. Performed to explore the effects of different intensities of geomagnetism on CUMS rats and the related molecular mechanisms. Results: The reults showed moderate geomagnetic storms (50 nT) protected against depressive behaviors in CUMS rats by increasing melatonin synthesis and metabolism and MT1 receptor pathway activity, while a extreme geomagnetic storms (500 nT) and shielding from geomagnetic storms (0 nT) inhibited melatonin synthesis and metabolism and the MT1 receptor pathway and aggravated injury. Conclusions: In this study we found moderate geomagnetic storms (50 nT) protected against depressive behaviors in CUMS rats, while a extreme geomagnetic storms (500 nT) and shielding from geomagnetic storms (0 nT) aggravated injury.